The effects of specific trainings applied to 14 age male soccer players on their balance, sprint and technical skills - Baydemir, B.; Alp, M. (Journal of Education and Training Studies, 2018)
The aim of this study was to investigate the effects of specific trainings applied to 14 age male soccer players on their balance, sprint and technical skills. 30 male soccer players, who attended the trainings at least 4 years in Çanakkale Besiktas Soccer School, joined to the study by having their parents confirm the "Parental Permission Form". Soccer players mean of length was calculated 158.24±2.98 cm and mean of weight was calculated 46.37±3.44 kg. Soccer-specific trainings were applied to the players 12 weeks, 3 days a week, at least 90 minutes a day. Flamingo balance, 30 meters sprint and technical skill tests were applied before and after the training period. Datas were analyzed in statistic package programme by using "Paired t Test". Results were evaluated according to "p<0.05" significance level. Significant differences were found in comparing the tests` results of soccer players (p<0.05). As a result, it can be said that the inclusion of high-intensity deflection exercises instead of the high-rigidity, flat running conditions applied in soccer-specific training has improved the technical skills of 14-year-old footballers and additionally affects their balance and speed performance positively.